PERAN COMMUNITY MARKETING DALAM MENUMBUHKAN VALUE CO-CREATION PADA PERUSAHAAN (STUDI KASUS PADA KOMUNITAS TEMAN BICARA): (STUDI KASUS PADA KOMUNITAS TEMAN BICARA) - Zumroti, Qurri Aini; S.Sos., M.I.Kom, Mutiah (Universitas Negeri Surabaya, 2024)
The development of the digital era is increasingly important for a company to have stakeholders who are able to encourage sales of its products or services. One of them is by utilizing the community as a way to conduct sales practices. But forming a community to play a role in the sales process also requires a strategy in it. Komunitas Teman Bicara is an organically formed community that the company considers to be able to grow value through the works made. This is also called value co-creation. This study aims to find out how the role of community marketing grows co-creation value at PT. Sinergi Bicara Indonesia through the Komunitas Teman Bicara. This type of research is descriptive qualitative using case study method. Data collection techniques are by observation, interviews and documentation. This research resulted in the Komunitas Teman Bicara formed emotional closeness formed by the company. Holding regular activities made by the community with the company is one way to become a community that is considered to play a role in fostering co-creation value.